The Dutch version of the Dignity Therapy Question Protocol for individual Dutch nursing home residents without cognitive impairments (during COVID-19): a pilot study - Herman van Dammen; Kris Vissers; Gert-Jan van der Putten; Yvonne Engels (BMC Geriatrics)
Abstract Background Dignity therapy is a brief, structured psychotherapeutic intervention originally designed to help last-stage cancer patients maintain their dignity. It consists of a semi-structured interview encouraging patients to talk about their lives. The recorded session are transcribed and edited, after which the patient has the opportunity to make further changes to the final document. It can be shared with whom the patient likes. We cross-culturally translated dignity therapy into Dutch and explored its feasibility of applying it to Dutch cognitively capable nursing home residents. Method Beaton’s Guidelines for Good Clinical Practice were used to cross-culturally translate dignity therapy. Next, a pilot study was conducted with 12 nursing home residents in which the original English-language questionnaire was transculturally translated according to the method of Beaton. After the interviews were completed, feasibility was examined by open-ended questions and a five-point Likert scale questionnaire. Results We translated the questionnaire. The translated questions were well understood and resulted in an appropriate Dutch version of the English-language dignity therapy questions. However, the words ‘dignity’ and ‘therapy’ caused confusion. The mean number of words in the legacy document was 1078 words, which appeared shorter than in a community-based hospice setting or patients with metastatic cancer or terminally ill people. The reading aloud was much appreciated and was an emotional experience for some. Conclusion We successfully translated the DTQP into the Dutch language and tested it in 12 nursing home residents. The questions posed by this therapy appeared suitable and acceptable. Furthermore, participants all accepted the therapy and gave no suggestions to adapt the procedure. Follow-up research in the form of an impact study is needed to show whether and how this therapy can strengthen the sense of dignity of Dutch nursing home residents.